Isolation and Insecticidal Activity of Essential Oil from Artemisia lavandulaefolia DC. against Plutella xylostella - Xing Huang; Yulin Huang; Chunyue Yang; Tiantian Liu; Xing Liu; Haibin Yuan (Toxins, 2021)
Many plants show significant biological activity against pests due to their unique chemical constituents. It is important to identify effective constituents for their development and utilization as botanical pesticides. Our previous study showed that Artemisia lavandulaefolia essential oil had biological activity against Plutella xylostella. Here, we isolated and identified the constituents of essential oil from A. lavandulaefolia by silica gel column chromatography. The main constituents identified were eucalyptol and caryophyllene oxide, and they were confirmed by gas chromatography–mass spectrometry (GC–MS). Eucalyptol and caryophyllene oxide showed strong contact toxicity against P. xylostella larvae after 24 h of application (Median lethal dose, LD50 = 76.97 μL/mL and 20.71 mg/mL. Furthermore, the two active constituents against P. xylostella adults showed significant fumigant activity (Mmedian lethal concentration, LC50 = 3.25 μL/L and 1.06 mg/L, respectively. Finally, we measured the detoxification enzymes and acetylcholinesterase of the larvae treated with active constituents. The eucalyptol-treated larvae displayed enhanced carboxylesterase (CarE) and glutathione-S-transferase (GST) activities in an in vivo experiment, but it was lower for acetylcholinesterase (AchE) activity. The activities of the CarE and GST significantly decreased when exposed to caryophyllene oxide. In general, the two active constituents, eucalyptol and caryophyllene oxide, showed high insecticidal activity, which demonstrates their potential to be used as natural insecticides.